2008 Fourth International Conference on Natural Computation 2008
DOI: 10.1109/icnc.2008.165
|View full text |Cite
|
Sign up to set email alerts
|

A Transport Mode Selection Method for Multimodal Transportation Based on an Adaptive ANN System

Abstract: Multimodal transportation is a complex network, in which all the components should be seamlessly linked and efficiently coordinated. Considered many noncommensurable, nonlinear even conflicting criteria simultaneously, the transport mode selection in multimodal transportation is studied within the framework of multicriteria decision making (MCDM). The theoretical basis for feedforward artificial neural network (FANN) to solve this MCDM problem is presented. With the initial topology predetermined by fuzzy anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…In addition, the optimization objects of the model include time, risk, carbon emission and environmental protection (Choong et al 2002;Verma, Verter 2010;Verma et al 2012;Demir et al 2016;Jiang, Zhang 2016;Seo et al 2017;Xia et al 2019). In terms of model establishment, the models are mainly in the form of integer programming, multi-model decisionmaking and mixed integer programming (Choong et al 2002;Qu et al 2008;Bierwirth et al 2012;Demir et al 2016). In algorithm design, adaptive neural network system, iterative decomposition method, tabu search algorithm and other heuristic algorithms are used to solve the problem (Qu et al 2008;Verma, Verter 2010;Verma et al 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the optimization objects of the model include time, risk, carbon emission and environmental protection (Choong et al 2002;Verma, Verter 2010;Verma et al 2012;Demir et al 2016;Jiang, Zhang 2016;Seo et al 2017;Xia et al 2019). In terms of model establishment, the models are mainly in the form of integer programming, multi-model decisionmaking and mixed integer programming (Choong et al 2002;Qu et al 2008;Bierwirth et al 2012;Demir et al 2016). In algorithm design, adaptive neural network system, iterative decomposition method, tabu search algorithm and other heuristic algorithms are used to solve the problem (Qu et al 2008;Verma, Verter 2010;Verma et al 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been found that all three models have almost 100% prediction accuracy at aggregate level. Qu et al (2008) set up Hybrid Multicriteria Decision Making (MCDM) on the basis of fuzzy analytic hierarchy process (AHP) and artificial neural net work (A NN) theory for route selection of multimodal transportation network. Sadeghi-Niaraki et al (2010) used multidimensional variables combined with multi-dimensional cost model (MCDM) to develop a road network cost function for route finding analysis in Iran.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Qu et al (2008) [7] stated that multimodal transportation is a complex network, in which all the components should be seamlessly linked and efficiently coordinated. The transport mode selection in multimodal transportation is studied within the framework of multicriteria decision making (MCDM).…”
Section: Literature Reviewmentioning
confidence: 99%